Concept of Self Medication: A Review - Jain, Sonam (International Journal of Pharmaceutical & Biological Archive, 2011)
This article presents a review on self medication, which can be defined as the use of medicine without any professional supervision. It aims to find the reason of self medication and make public aware about its effects and side effects. People use it for the treatment of any disease symptoms or minor ailments by their self initiative. The most commonly available OTC medications are pain killers, cough and cold remedies, anti-allergy medicines, vitamins and energy tonics. Although these medications are considered risk free and useful for the treatment of common health problems, their excessive use can also lead to serious side effects and unfavorable reactions. The percentage of self medication might be changes with locality and region. Prevalence of self medication is high in professional students. Many of the national and international journals on the self medication were reviewed for their findings and report on different parameters. There are several drug stores, which provide the medicine without any prescription and its percentage is increasing day to day in India. Presently the frequency is high of self medication by the young ones and literate people who do not have much time to go to physician. This review conclude the benefit (when drug is used in limit and its use, characteristics are known), drawback (when people have no idea about its use and limitations) of drugs and their safe use.